A critical appraisal of some aspects of the Prevention of Domestic Violence Act of Sri Lanka in the context of gender equality - Wijeyesekera, Rose (My University, 2011)
Domestic violence is the most prevalent yet relatively hidden and ignored form of violence. It is recognized internationally that domestic violence, irrespective of its form, is a denial of equality, security, self-worth and fundamental freedom, and that the states are obliged to curb such violence. The conventional justice system including the existing criminal and civil laws have proved insufficient to address this issue due to various reasons. Thus, the necessity to have an effective law on domestic violence arose. Partly in recognition of this reality and partly on the international pressure, the Parliament of Sri Lanka enacted the Prevention of Domestic Violence Act. The Act however, has not proved as effective as expected. This article intends to appraise the strength of the Act in two aspects: 1) The gender neutral approach of the Act and its real impact on women in the context of a patriarchal society, 2) The failure of the Act to provide for the protection of victims in absence of a system where effective legal aid, support and healing services are guaranteed. These will be substantiated by examples from similar statutes from other jurisdictions. In conclusion, it is intended to establish that the law should guarantee substantial equality as opposed to formal equality for women in order to ensure equal justice and that the effective involvement of the substance, structure and the culture of the law are essential in order to attain effective results from the law.